I shall find the integral by Feynman’s Technique Integration on a particular integral

$\displaystyle I(a)=\int_{0}^{\pi} \ln (a \cos x+1) d x,\tag*{} $ where $-1\leq a \leq 1.$ $\displaystyle \begin{aligned}I^{\prime}(a) &=\int_{0}^{\pi} \frac{\cos x}{a \cos x+1} d x, \\&=\frac{1}{a} \int_{0}^{\pi} \frac{(a \cos x+1)-1}{a \cos x+1} d x \\&=\frac{\pi}{a}-\frac{1}{a} \int_{0}^{\pi} \frac{d x}{a \cos x+1} \\&\stackrel{t=\tan \frac{x}{2}}{=} \frac{\pi}{a}-\frac{1}{a} \int_{0}^{\infty} \frac{1}{1+\frac{a\left(1-t^{2}\right)}{1+t^{2}}} \cdot \frac{2 d t}{1+t^{2}} \\&=\frac{\pi}{a}-\frac{2}{a} \int_{0}^{\infty} \frac{d t}{(1-a) t^{2}+(1+a)} \\&=\frac{\pi}{a}-\frac{2}{a \sqrt{1-a^{2}}} \tan^{-1}\left[\frac{\sqrt{1-a} t}{\sqrt{1+a}}\right]_{0}^{\infty} \\&=\frac{\pi}{a}-\frac{\pi}{a \sqrt{1-a^{2}}}\end{aligned}\tag*{} $ Integrating both sides w.r.t. $a$ yields \begin{aligned}\int I^{\prime}(a) d a &=\pi\int\left(\frac{1}{a}-\frac{1}{a \sqrt{1-a^{2}}}\right) da \\& \stackrel{a=\sin \theta}{=} \pi\int\left(\frac{1}{\sin \theta}-\frac{1}{\sin \theta \cos \theta}\right) \cos \theta d \theta \\&=\pi\int \frac{\cos \theta-1}{\sin \theta} d \theta\\&I(a) =\pi \int \frac{-\sin ^{2} \theta}{\sin \theta(\cos \theta+1)} d \theta\\&=\pi \ln (1+\cos \theta) +C\end{aligned} Putting $a=0$ gives $C=-\pi\ln 2$ and hence

$$ \boxed{\int_{0}^{\pi} \ln (a \cos x+1) d x =\pi \ln \left[1+\cos \left(\sin ^{-1} a\right)\right]= \pi \ln \left(\frac{1+\sqrt{1-a^{2}}}{2} \right)} $$

I now want to generalize it to $$I(b,c)=\displaystyle \int_{0}^{\pi} \ln (b \cos x+c),\tag*{} $$

where $c\neq 0$ and $-1\leq \frac{b}{c} \leq 1.$

$$ \begin{aligned} I(b,c)&=\int_{0}^{\pi} \ln (b \cos x+c) \\ &=\int_{0}^{\pi} \ln \left[c\left(\frac{b \cos x}{c}+1\right)\right] \\ &=\pi \ln c+\int_{0}^{\pi} \ln \left(\frac{b}{c} \cos x+1\right) d x \\ &=\pi \ln c+I\left(\frac{b}{c}\right) \end{aligned} $$

Putting $a=\frac{b}{c}$ yields $$\boxed{\int_{0}^{\pi} \ln (b \cos x+c) = \pi\left[\ln c+\ln \left(1+\sqrt{1-\frac{b^{2}}{c^{2}}}\right)\right] = \pi \ln \left(\frac{c+\sqrt{c^{2}-b^{2}}}{2}\right)} $$

For example,

$$ \int_{0}^{\pi} \ln (\cos x+1)=\pi \ln \left(\frac{1}{2}\right)=-\pi \ln 2; $$

$$ \int_{0}^{\pi} \ln (\sqrt{3} \cos x+2) d x=\pi\ln \frac{3}{2} $$

Is there any method other than Feynman’s integration technique?


4 Answers 4


Concerning the antiderivative $$I=\int \log (b \cos (x)+c)\,dx=2\int \frac 1{t^2+1}\Big[\log[ (c-b)t^2+(b+c)]-\log(t^2+1)\Big]\,dt$$ But $$\log[ (c-b)t^2+(b+c)]=\log(c-b)+\log \left(t-\sqrt{\frac{b+c}{b-c}}\right)+\log \left(t+\sqrt{\frac{b+c}{b-c}}\right)$$

Now, using $$\frac 1{t^2+1}=\frac 1{(t+i)(t-i)}=\frac i2 \left(\frac{1}{t+i}-\frac{1}{t-i}\right)$$ we face four integrals $$J(\alpha,\beta)=\int \frac {\log(t+\alpha)}{t+\beta}\,dt=\text{Li}_2\left(\frac{t+\alpha }{\alpha -\beta }\right)+\log (t+\alpha ) \log \left(\frac{\beta +t}{\beta -\alpha }\right)$$


Note that, with $r= \frac cb -\sqrt{\frac{c^2}{b^2}-1}$ $$\ln (b \cos x+c)=\ln\frac{c+\sqrt{c^2-b^2}}2+\ln\left(1+2r\cos x+r^2\right) $$ Thus, per $\int_0^\pi \ln\left(1+2r\cos x+r^2\right)dx=0$ $$\int_{0}^{\pi} \ln (b \cos x+c)dx =\pi \ln\frac{c+\sqrt{c^2-b^2}}2 $$

  • 2
    $\begingroup$ A nice approach. For $c>b\,$ I used $$\frac{b}{2}(e^{ix}+e^{-ix})+c=\frac{c+\sqrt{c^2-b^2}}{2}\Big(1+\frac{b}{c+\sqrt{c^2-b^2}}e^{ix}\Big)\Big(1+\frac{b}{c+\sqrt{c^2-b^2}}e^{-ix}\Big)$$ and, decomposing logarithms, $\int_0^{2\pi}e^{inx}dx=0;\,\, n=1,2,...$ $\endgroup$
    – Svyatoslav
    Jun 12 at 13:39

Another option as opposed to using an infinite sequence and piecewise integration is to use a Weierstrass substitution and then a double integral.

Take $x\mapsto\tan\left(\tfrac x2\right)$ such that $\cos x\mapsto(1-x^2)/(1+x^2)$. The integral then becomes

$$\begin{align*}I & \equiv\int\limits_0^\pi\mathrm dx\,\log(1+a\cos x)\\ & =2\int\limits_0^{+\infty}\frac {\mathrm dx}{1+x^2}\log\left(1+a\frac {1-x^2}{1+x^2}\right)\\ & =2\int\limits_0^{+\infty}\frac {\mathrm dx}{1+x^2}\left[\log(1+a)+\log\left(1+\frac {1-a}{1+a}x^2\right)-\log(1+x^2)\right]\end{align*}$$

The first integral is trivial

$$\log(1+a)\int\limits_0^{+\infty}\frac {\mathrm dx}{1+x^2}=\frac \pi2\log(1+a)$$

The last two integrals can be evaluated using the general case

$$J\equiv\int\limits_0^{+\infty}\mathrm dx\,\frac {\log(1+z^2 x^2)}{1+x^2}$$

With the middle integral being the special case $z^2=(1-a)/(1+a)$ and the last integral being the case $z=1$. To evaluate $J$, we make use of a double integral, namely

$$\log(1+z^2)=\int\limits_0^1\mathrm dy\,\frac {2yz^2}{1+y^2z^2}$$

Substituting the identity above into $J$ and switching the order of integration gives

$$\begin{align*}J & =\int\limits_0^1\mathrm dy\,\int\limits_0^{+\infty}\mathrm dx\,\frac {2x^2yz^2}{(1+x^2)(1+x^2y^2z^2)}\\ & =\int\limits_0^1\mathrm dy\,\frac {2yz^2}{y^2z^2-1}\int\limits_0^{+\infty}\mathrm dx\,\left(\frac 1{1+x^2}-\frac 1{1+x^2y^2z^2}\right)\\ & =\pi z^2\int\limits_0^1\mathrm dy\,\frac y{y^2z^2-1}\left(1-\frac 1{yz}\right)\\ & =\pi z\int\limits_0^1\frac {\mathrm dy}{1+yz}\\ & =\pi\log(1+z)\end{align*}$$


$$\int\limits_0^{+\infty}\frac {\mathrm dx}{1+x^2}\log\left(1+\frac {1-a}{1+a}x^2\right)=\pi\log\left(1+\sqrt{\frac {1-a}{1+a}}\right)$$


$$\int\limits_0^{+\infty}\frac {\mathrm dx}{1+x^2}\log(1+x^2)=\pi\log 2$$

Putting everything together, then

$$\int\limits_0^\pi\mathrm dx\,\log(1+a\cos x)\color{blue}{=\pi\log\left(\frac {1+a}4\right)+2\pi\log\left(1+\sqrt{\frac {1-a}{1+a}}\right)}$$

Let $a=1$ and we get the integral stated in the question

$$\int\limits_0^\pi\mathrm dx\,\log(1+\cos x)=\pi\log\left(\frac 12\right)=-\pi\log 2$$

The more general case considering $\log(a+b\cos x)$ can be evaluated by transforming the integrand such that the constant term becomes one. Factoring out an $a$ gives

$$K\equiv\int\limits_0^\pi\mathrm dx\,\log(a+b\cos x)=\pi\log a+\int\limits_0^\pi\mathrm dx\,\log\left(1+\frac ba\cos x\right)$$

Using the formula we derived above and after some simplification, then

$$\int\limits_0^\pi\mathrm dx\,\log(a+b\cos x)\color{blue}{=\pi\log\left(\frac {a+b}4\right)+2\pi\log\left(1+\sqrt{\frac {a-b}{a+b}}\right)}$$

Substituting $a=2$ and $b=\sqrt3$ gives

$$\int\limits_0^\pi\mathrm dx\,\log(2+\sqrt3\cos x)=\pi\log\left(\frac {2+\sqrt3}4\right)+2\pi\log\left(1+\sqrt{\frac {2-\sqrt3}{2+\sqrt3}}\right)=\pi\log\left(\frac 32\right)$$


You can use Chebyshev polynomials of the second kind. The identity

$$ U_n(x) = 2^n \prod_{k=1}^{n}\left(x-\cos\frac{\pi k}{n+1}\right) $$

leads to

$$\log U_n(A) = n\log 2+\sum_{k=1}^{n}\log\left(A-\cos\frac{\pi k}{n+1}\right) $$

then to

$$ \int_{0}^{\pi}\log(A-\cos\theta)\,d\theta = -\pi\log 2+\lim_{n\to +\infty}\frac{\pi \log U_n(A)}{n+1} $$

for any $A>1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.